2003
DOI: 10.1063/1.1593830
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress effect on imprint behavior of integrated ferroelectric capacitors

Abstract: Kingon, A. I.; Nemanich, R. J.; Tagantsev, A. K.; Cross, J. S.; and Tsukada, M., "Mechanical stress effect on imprint behavior of integrated ferroelectric capacitors" (2003). Alexei Gruverman Publications. 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(179 citation statements)
references
References 22 publications
10
164
1
4
Order By: Relevance
“…Vertical PFM ͑VPFM͒ and lateral PFM ͑LPFM͒ imaging methods, used to detect out-of-plane and in-plane polarization components, respectively, have been described in detail elsewhere. [5][6][7][11][12][13][14][15][16][17][18] The modulation voltage ͑typically 0.6 Vrms at 10 kHz͒ was applied to the top electrode of the capacitor using a conduca͒ Author to whom correspondence should be addressed; electronic mail: alexei -gruverman@ncsu.edu tive PFM tip, which was also used to detect the piezoelectric response of the capacitor. Commercially available Pt-coated Si rectangular cantilevers ͑1.0-2.6 N/m force constant͒ have been used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertical PFM ͑VPFM͒ and lateral PFM ͑LPFM͒ imaging methods, used to detect out-of-plane and in-plane polarization components, respectively, have been described in detail elsewhere. [5][6][7][11][12][13][14][15][16][17][18] The modulation voltage ͑typically 0.6 Vrms at 10 kHz͒ was applied to the top electrode of the capacitor using a conduca͒ Author to whom correspondence should be addressed; electronic mail: alexei -gruverman@ncsu.edu tive PFM tip, which was also used to detect the piezoelectric response of the capacitor. Commercially available Pt-coated Si rectangular cantilevers ͑1.0-2.6 N/m force constant͒ have been used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Among the accomplishments of the PFM approach is an insight into spatial variability issues of ferroelectric capacitors. [8][9][10][11][12] In addition, the role of mechanical stress in the spatial inhomogeneity of switching behavior in ferroelectric capacitors has recently been emphasized by PFM. 10,11 To better understand a nanoscale mechanism of switching in polycrystalline films it would be helpful to reconstruct the three-dimensional domain arrangement at the subgrain level.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the flexoelectricity-induced electric field could be large and tunable in ferroelectric HoMnO 3 epitaxial thin films. They directly estimated the flexoelectricity-driven electric field using the equation [18,42] …”
Section: (B) Domain Configurationsmentioning
confidence: 99%
“…The origin of the self-polarization in ferroelectric thin films has been discussed in terms of different mechanisms such as Schottky barriers, 22 lead vacancies, 23 mechanical coupling between the film and the substrate, 24 formation temperature of the ferroelectric phase, 25 and some others. When the top and bottom electrodes of a metal/ferroelectric/ metal configuration are made of different materials, trapped charges appear near the bottom ferroelectric-electrode interface leading to a build-in electric field responsible for the self-polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Such defects appear in these materials due to several factors such as PbO loss and oxygen pressure during the synthesis or donor/acceptor impurities introduced in the perovskite ABO 3 structure. 24 Additionally, strain gradients along the film depth sometimes appear in epitaxial films due to a perfect match between lattice parameters of film-substrate. This strain gradient is another mechanism responsible for the self-polarization.…”
Section: Resultsmentioning
confidence: 99%